Gas-Sensing Performances of Metal Oxide Nanostructures for Detecting Dissolved Gases: A Mini Review - Guan, Wei; Tang, Na; He, Kuang; Hu, Xiaoying; Li, Mingshan; Li, Kaiming (Frontiers in Chemistry, 2020)
Gas sensors have been wildly used in various fields related to people's lives. Gas sensor materials were the core factors that affected the performances of various gas sensors, and these have attracted much attention from scientific researchers due their high sensitivity, high selectivity, adjustable reliability, low cost, and other advantages. The preparation of nanostructures with a highly specific surface area was a useful method to improve the gas-sensing performance of a metal oxide semiconductor. Meanwhile, lots of research has focused on preparing nanostructures with a highly specific surface area. This paper has explored some fabricated sensors with high sensitivity, good selectivity, and long-term stability, which has also made them promising candidates for toxic gas detection. Besides, this paper has reviewed the development status of metal oxides used as gas sensors.